2000
DOI: 10.1002/j.2161-0045.2000.tb00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Transition Planning for Students With Learning Disabilities

Abstract: Many transition plans for students with learning disabilities suffer because (a) they often focus on the employment needs of students with more severe cognitive and physical disabilities and (b) they are not required until as late as 14 years old, sometimes too late for many students with learning disabilities. Lack of effective transition planning may result in inadequate postsecondary adjustment problems (e.g., under‐ or unemployment, restricted participation in community and leisure activities). The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
(48 reference statements)
1
26
0
3
Order By: Relevance
“…Recommendations are presented to address the continuing problem of preparing students with disabilities for postsecondary education. Overall, the matriculation of students with disabilities to postsecondary education has increased dramatically over the past 25 years, but enrollment continues to be low relative to students without disabilities (Cummings, Maddux, & Casey, 2000;Kavale & Forness, 1996). The number of first-year students with disabilities has risen from between 1% and 3% in 1978 to 6.5% in 1988 and 8.2% in 1994, with slight declines to 7.1% in 1998 and 6.0% in 2000 (Henderson, 1998(Henderson, , 2001Wagner, D'Amico, Marder, Newman, & Blackorby, 1992).…”
Section: W E Hitchings Paul Retish Michael Horvathmentioning
confidence: 99%
“…Recommendations are presented to address the continuing problem of preparing students with disabilities for postsecondary education. Overall, the matriculation of students with disabilities to postsecondary education has increased dramatically over the past 25 years, but enrollment continues to be low relative to students without disabilities (Cummings, Maddux, & Casey, 2000;Kavale & Forness, 1996). The number of first-year students with disabilities has risen from between 1% and 3% in 1978 to 6.5% in 1988 and 8.2% in 1994, with slight declines to 7.1% in 1998 and 6.0% in 2000 (Henderson, 1998(Henderson, , 2001Wagner, D'Amico, Marder, Newman, & Blackorby, 1992).…”
Section: W E Hitchings Paul Retish Michael Horvathmentioning
confidence: 99%
“…Past research has shown that the transition from school to adulthood for individuals with disabilities is facilitated by multiple factors, at least in the short run, including postsecondary education, employment, social participation (Cummings, Maddux, & Casey, 2000), and parental involvement (Morningstar, Turnbull, & Turnbull, 1995). Our findings offer a longer lens on these issues, extending into midlife, and thus underscore the lasting importance of key social institutions in the lives of individuals with mild intellectual deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Students with disabilities identify different patterns of personal interests and activities, as well as postsecondary training after high school (Chambers, Rabren, & Dunn, 2009). Young adults with disabilities, however, may not be aware of personal strengths and limitations (Cummings, Maddux, & Casey, 2000). Research indicates that several factors also influence one's work personality.…”
Section: Work Adjustmentmentioning
confidence: 99%